Dietary phosphatidylcholine impacts on growth performance and lipid metabolism in adult Genetically Improved Farmed Tilapia (GIFT) strain of Nile tilapia Oreochromis niloticus. Issue 1 (11th December 2017) - Tian, Juan; Wen, Hua; Lu, Xing; Liu, Wei; Wu, Fan; Yang, Chang-Geng; Jiang, Ming; Yu, Li-Juan
Abstract: This study aimed to determine the effects of supplementing the diet of adult Nile tilapia Oreochromis niloticus with phosphatidylcholine (PC) on growth performance, body composition, fatty acid composition and gene expression. Genetically Improved Farmed Tilapia fish with an initial body weight of 83·1 (sd 2·9) g were divided into six groups. Each group was hand-fed a semi-purified diet containing 1·7 (control diet), 4·0, 6·5, 11·5, 21·3 or 41·0 g PC/kg diet for 68 d. Supplemental PC improved the feed efficiency rate, which was highest in the 11·5 g PC/kg diet. Weight gain and specific growth rate were unaffected. Dietary PC increased PC content in the liver and decreased crude fat content in the liver, viscera and body. SFA and MUFA increased and PUFA decreased in muscle with increasing dietary PC. Cytoplasmic phospholipase A 2 and secreted phospholipase A 2 mRNA expression were up-regulated in the brain and heart in PC-supplemented fish. PC reduced fatty acid synthase mRNA expression in the liver and visceral tissue but increased expression in muscle. Hormone-sensitive lipase and lipoprotein lipase expression increased in the liver with increasing dietary PC. Growth hormone mRNA expression was reduced in the brain and insulin-like growth factor-1 mRNA expression in liver reduced with PC above 6·5 g/kg. Our results demonstrate that dietary supplementation with PC improves feed efficiency and reduces liver fat in adult Nile tilapia, without increasing weight gain, representing a novel dietary approach to reduce feed requirements and improve the health of Nile tilapia.